Avalia??o anti-helm?ntica e toxicol?gica de extratos e fra??es do res?duo de Agave Sisalana Perr. (SISAL) sobre nematoides gastrintestinais de caprinos - Botura, Mariana Borges (2011)
This study describes the evaluation of extracts and fractions of Agave sisalana (sisal) on gastrointestinal nematodes and their toxic effects in goats. The in vitro anthelmintic activity of aqueous (AE), ethyl acetate (EE) extracts, flavonoids (FF) and saponins fractions (SF) obtained from sisal residue were determined through the egg hatch assay (EHA) and L3 migration inhibition (LMI). For the in vivo test, 30 animals were distributed into three groups: GI, was treated with AE (1.7 g/kg/day) for eight days; GII, was treated with levamisole; and GIII, was left untreated. The cytotoxic effects of extracts and fractions were investigated in Vero cells by MTT and trypan blue tests. The EC50 on eggs were 4.7, 0.1 and 0.05 mg/mL for AE, EE and FF, respectively. In the LMI, the greatest efficacy was observed in the SF (64.1%). In vivo evaluation, the reductions of faecal eggs counts were 50.3 (GI) and 93.6 (GII), and of the total number of L3 larvae were 80 (GI) and 85.6 (GII). The AE did not affect the count of adult parasites. The AE, EE, and SF were cytotoxic, with IC50 of 570, 180 and 13.7 mg/mL, respectively. The sisal showed ovicidal action and the analysis of the most active fraction (FF) indicates the presence of a homoisoflavonoid. The in vitro effect on larvae and Vero cells is related to the saponinas fraction. The in vivo anthelmintic treatment with AE showed moderate activity against eggs and free-living stages, with no evidence of toxicity.